A Triadic (3-Dimensional) Philosophical Approach to Acne (Homoeopathy for All, 2025)
Acne is one of the most common  dermatological conditions affecting  adolescents and adults alike, often  impacting physical appearance,  self-esteem, and quality of life. It  is often considered as a cosmetic  concern. The complex interplay of  genetics, temperament, digestive  and hormonal equilibrium, and  mental state underlies the visible  eruptions such as papules, pustules,  and cysts. Conventional perspectives  emphasise hormonal, dietary, and  microbial factors; however, the  complexity of acne transcends these  superficial explanations. Conventional therapeutic  guidelines recommend the use of  topical and oral retinoids, antibiotics,  benzoyl peroxide, azelaic acid,  chemical peels, and light therapy,  among other treatments. Patients  have progressively begun exploring  complementary and alternative  medicine (CAM) options, including  homeopathy., , Worldwide,  homeopathy is considered the  second most prevalent kind of  complementary and alternative  medicine utilised by outpatient  dermatology patients, with acne  being the most often treated condition  through CAM therapy. Evidence  indicates that homeopathy can  enhance the condition of acne and  its associated scars, hence justifying  treatment for these patients. Patients  are increasingly seeking therapies  that they believe provide relief with  minimal adverse effects, for which  homeopathy is renowned.
Keywords: physical appearance; complementary and alternative medicine; homeopathy; external manifestation